A Rare Interstitial Duplication of 8q22.1–8q24.3 Associated with Syndromic Bilateral Cleft Lip/Palate - Regina Ferreira Rezek; Ana Angélica Rodrigues Abbas; Juliana Forte Mazzeu; Siliana Maria Duarte Miranda; Cibele Velloso-Rodrigues (Case Reports in Dentistry)
We present a rare case of 8q interstitial duplication derived from maternal balanced translocations in a patient with bilateral cleft lip and palate in syndromic form associated with other congenital malformations. G-banding cytogenetic analysis revealed a chromosomal abnormality in the form of the karyotype 46,XX der(22)t(8;22)(q22.1;p11.1)mat. Chromosome microarray analysis evidenced a 49 Mb duplicated segment of chromosome 8q with no pathogenic imbalances on chromosome 22. Two siblings also carry the balanced translocation. We have compared this case with other “pure” trisomies of 8q patients reported in the literature and with genome wide association studies recently published. This work highlights the involvement of chromosome 8q in orofacial clefts.